Solve for L
L=-\frac{xz\epsilon }{sx+t}
\epsilon \neq 0\text{ and }t\neq -sx
Share
Copied to clipboard
\left(sx+t\right)L=\epsilon \left(0I-xz\right)
Multiply both sides of the equation by \epsilon \left(sx+t\right), the least common multiple of \epsilon ,t+xs.
sxL+tL=\epsilon \left(0I-xz\right)
Use the distributive property to multiply sx+t by L.
sxL+tL=\epsilon \left(0-xz\right)
Anything times zero gives zero.
sxL+tL=\epsilon \left(-1\right)xz
Anything plus zero gives itself.
\left(sx+t\right)L=\epsilon \left(-1\right)xz
Combine all terms containing L.
\left(sx+t\right)L=-xz\epsilon
The equation is in standard form.
\frac{\left(sx+t\right)L}{sx+t}=-\frac{xz\epsilon }{sx+t}
Divide both sides by t+xs.
L=-\frac{xz\epsilon }{sx+t}
Dividing by t+xs undoes the multiplication by t+xs.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}